2018
DOI: 10.1016/j.tra.2018.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships between operators and public transport authorities. Working practices in relational contracting and collaborative partnerships

Abstract: Recent research on public transport has seen increasing focus on issues like coordination, collaboration and steering in complex governance settings. One of the themes in this field of research is related to partnership approaches, as one way of stimulating functioning collaboration between formally independent private and public organisations. The aim of this paper is to explore the role and function of partnerships as a way of supporting wellfunctioning public transport networks and services in fragmented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
10
0
4
Order By: Relevance
“…In recent years there have been some developments that highlight the use of the BIM methodology as a collaborative tool (Liu et al, 2017) to create an information centre for the life cycle of projects (Mihic et al, 2014), where stakeholders add information or knowledge to the model (Hrelja et al, 2018), from which all the necessary documents are then extracted of focal points, including the impact upon information and transactions costs, for example, game theory is often used to study the relationship among engineering project stakeholders and resolve conflicts (Rzepecki, 2021). The review of modern application of a game theory has shown the wide spectrum Table 1.…”
Section: Relational Contracting In Combination With the Bim Methodology In Reducing Asymmetric Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years there have been some developments that highlight the use of the BIM methodology as a collaborative tool (Liu et al, 2017) to create an information centre for the life cycle of projects (Mihic et al, 2014), where stakeholders add information or knowledge to the model (Hrelja et al, 2018), from which all the necessary documents are then extracted of focal points, including the impact upon information and transactions costs, for example, game theory is often used to study the relationship among engineering project stakeholders and resolve conflicts (Rzepecki, 2021). The review of modern application of a game theory has shown the wide spectrum Table 1.…”
Section: Relational Contracting In Combination With the Bim Methodology In Reducing Asymmetric Informationmentioning
confidence: 99%
“…In other words, the IPD is a RC approach that aligns the project goals with the stakeholders' interests (Matthews & Howell, 2005). Relational contracting is relevant to the IPD methodology because changing assumptions about the stakeholders' behaviours and motivations allows envisaging and addressing many of the problems associated with public-private supply (Hrelja et al, 2018). Piroozfar et al (2019) also point out that collaboration and trust are the most important factors of the IPD methodology in the project's initial stage.…”
Section: Relevance Of Relational Contracting In Reducing Asymmetric Informationmentioning
confidence: 99%
“…PPP stakeholders are committed to a long-term relationship with each other, and communication is an effective way to maintain this relationship. Poor communication between the government and the social sectors hampers decision making and successful operation of PPP projects [51].…”
Section: Managing Risk (Mr)mentioning
confidence: 99%
“…Par exemple, dans le Royaume-Uni des années Thatcher, la privatisation ferroviaire s'est traduite par une telle suite d'incidents et d'accidents que les géographes n'ont eu aucun mal à relier la crise technique du système ferroviaire à sa privatisation. Cependant, notre approche s'inspire plutôt des travaux en science de la planification, au sein desquels le succès et l'échec sont toujours relatifs et constitutifs de l'action publique 3 Cette recherche convoque les notions de policy learning 4 , de policy failure 5 , et de network governance 6 . À partir d'une vingtaine d'entretiens approfondis, et après une présentation de la notion d'échec au travers de l'idée d'infrastructure critique (partie 1), nous testons la double hypothèse suivante :…”
unclassified
“…La dynamique institutionnelle qui constitue l'expertise comme un enjeu de pouvoir crée ses propres contrepoids à travers la prolifération d'instances et d'outils qui mettent en scène des postures de médiation et de proximité. Pour Hrelja17 comme pour Steele et Legacy18 , la gouvernance partenariale en réseau qui émerge dans les systèmes de transports collectifs correspond à une adaptation pragmatique des acteurs face à la montée en puissance de l'expertise et à l'institutionnalisation des relations de pouvoir entre organisateurs, gestionnaires et opérateurs. Les agents mettent de l'huile dans les rouages à mesure que leurs institutions s'affrontent.…”
unclassified